Impacts of Surface Water Quality in the Awash River Basin, Ethiopia: A Systematic Review - Assegide, Endaweke; Alamirew, Tena; Bayabil, Haimanote; Dile, Yihun T.; Tessema, Bezaye; Zeleke, Gete (Frontiers in Water, 2022)
Water quality impairment due to pollution is a rapidly growing threat to water security as well as public health to developing countries due to the limited enforcement capacity of regulatory organizations. The problem is severe for rivers like Awash in Ethiopia that pass through cities. Although a number of investigations into the state of pollution have been made, they tend to be location, tributary, or season-specific. A recent systematic analysis of the different works and generating comprehensive information and recommendation for actions is still imperative. It was found from the different published and gray literature that water quality degradation along the river course and in selected tributaries exceed the WHO and national guidelines. Bacteriologically, the E-coli bacteria concentration in Tinishu and Tiliku Akaki reach up to 6.68 and 6.61 billion CFU 100ml/L. Virological quality of creeks receiving wastewater from hospitals in Addis Ababa contains coliphages enumerations reaching as high as 5.2×103 pfu/100ml for urban rivers and up to 4.92×103 pfu/100 ml. The vegetables produced using water from tributaries contain heavy metals like Cd, Cr, Cu, Hg, Ni, and Zn in potato, Zn and Hg in Cabbage, and Cr in onion and red beet that far exceeds the tolerable levels for humans and the ecosystems. Lettuce irrigated with Akaki river water found to contain 0.263 (Cd), 420 (Fe), 13.44 (Zn), 7.87 (Cr), 7.49 (Cu), and 6.55 (Pb) mg/kg both in excess of WHO guideline. The review exhibits the need for urgent action particularly in selected tributaries that passes through industrial zones and receiving untreated urban wastewater. Comprehensive water quality investigation that takes into account the different pollutants dynamic needs to be made to protect the wellbeing of downstream beneficiaries including the aquatic ecosystem.